Workplace policies and practices promoting physical activity across England: what is commonly used and what works? - Knox, Emily; Musson, Hayley; Adams, Emma (Emerald, 2018)
Purpose Many adults fail to achieve sufficient moderate-to-vigorous physical activity (MVPA). Understanding how workplaces most effectively promote physical activity can benefit public health. Design/methodology/approach Data were collected via two online surveys. Firstly, 3,360 adults employed at 308 workplaces across England self-reported their MVPA, activity status at work and frequency of journeys made through active commuting. From this sample, 588 participants reported on the policies and practices used in their workplace to promote physical activity. Factor and cluster analysis identified common practice. Regression models examined the association between the workplace factors and engagement in physical activity behaviours. Findings Five factors emerged: targeting active travel, information about physical activity outside the workplace, facilities and onsite opportunities, sedentary behaviour, and information about physical activity within the workplace. Further, five clusters were identified illustrate how the factors are typically being utilised by workplaces across England. Commonly used practices related to promoting active travel,reducing sedentary behaviour and the provision of information but these practices were not associated with meeting MVPA guidelines. The provision of facilities and onsite exercise classes was associated with the most positive physical activity behaviour outcomes; however, these structures were rarely evident in workplaces. Originality/value. Previous research has identified a number of efficacious actions for promoting physical activity in the workplace, however, research investigating which of these are likely to be acceptable to worksites is limited. The present study is the first to combine these two important aspects. Five common profiles of promoting physical activity in worksites across England were identified and related to physical activity outcomes. Guidance is given to workplace managers to enable them to maximise the resources they have for the greatest gains in employee health. Where feasible, facilities and classes should be provided to achieve the most positive outcomes.